Multimedia y aprendizaje de las operaciones con matrices en los estudiantes universitarios - Quiroz Chavil, Helga Kelly (2014)
This pre-experimental research is conducted because of the deficiencies of the students for learning matrix operations so we set ourselves the objective to determine the influence of the application of multimedia learning program matrix operations in students the first semester of the Professional School of Civil Engineering of the Universidad César Vallejo, in the academic year 2012-I. The population consisted of 21 students to whom a questionnaire was applied: "Evaluation of the learning matrix operations", which had a reliability of 0.85 (Cronbach) type examinations which evaluated students before and after applying the program. ethical principles were applied and the results revealed that after following the program using the multimedia learning students improved, increasing markedly in the levels of measured learning because from the scale of learning achieved, from 0% obtained in the pretest, amounted to 71.4% in the post test, as for the learning process rises 14.3% to 28.6%, but above all, we can see a significant improvement when comparing the percentages learning not attained that 85.7% in the pre-test goes to 0% in the post test. Allowing concludes that the multimedia program based on the proposed Vigonsky facilitates interpersonal and intrapersonal processes of learning, promotes self-assessment and self-learning, allowing it to reach the powers provided.